IMPACT OF BILIARY ETIOLOGY ON THE OUTCOME OF ACUTE PANCREATITIS - Fahad Hafeez khan; Gohar latif Kalas; Kamran Hakeem Khan et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: To determine the impact of biliary etiology on the outcome of acute pancreatitis. STUDY DESIGN: Randomized controlled trial PLACE & DURATION OF STUDY: Study was conducted at Department of General Surgery, Pakistan Institute of Medical Sciences, Islamabad from January 2013 to January 2014. METHODOLOGY: A total of one hundred and sixty (n=160) patients of both genders having age >13 years presented with acute pancreatitis were enrolled and randomly divided in two groups A (biliary etiology) and B (non-biliary etiology). Outcomes in both groups were noted in terms of analgesia requirement, hospital stay, need for assisted ventilation, oxygen inhalation and occurrence of local and systemic complications etc. Student t-test and chi-square test was used to analyze data. P-value <0.05 considered as signiﬁcant. RESULTS: Oxygen was required in 60% of patients in group A while 48.75% in group B during their stay at hospital. Frequency of patients who discharged within one week of admission, need ventilator support and operative management found to be 37.5%, 30% and 47.5% in group A while 47.5 %, 15% and 15% respectively in group B. CONCLUSION: Fewer complications were associated with non-biliary etiology. Frequency of favorable outcome was lower in the patients with biliary etiology.